Adjuvant and salvage radiotherapy after prostatectomy: a systematic review and meta-analysis. - Changhao Chen; Tianxin Lin; Yu Zhou; Doudou Li; Kewei Xu; Zhihua Li; Xinxiang Fan; Guangzheng Zhong; Wang He; Xu Chen; Xianyin He; Jian Huang (PLoS ONE)
Purpose In men with adverse prognostic factors (APFs) after radical prostatectomy (RP), the most appropriate timing to administer radiotherapy remains a subject for debate. We conducted a systemic review and meta-analysis to evaluate the therapeutic strategies: adjuvant radiotherapy (ART) and salvage radiotherapy (SRT). Materials and methods We comprehensively searched PubMed, EMBASE, Web of Science and the Cochrane Library and performed the meta-analysis of all randomized controlled trials (RCTs) and retrospective comparative studies assessing the prognostic factors of ART and SRT. Results Between May 1998 and July 2012, 2 matched control studies and 16 retrospective studies including a total of 2629 cases were identified (1404 cases for ART and 1185 cases for SRT). 5-year biochemical failure free survival (BFFS) for ART was longer than that for SRT (Hazard Ratio [HR]: 0.37; 95% CI, 0.30-0.46; p<0.00001, I(2) = 0%). 3-year BFFS was significantly longer in the ART (HR: 0.38; 95% CI, 0.28-0.52; p<0.00001, I(2) = 0%). Overall survival (OS) was also better in the ART (RR: 0.53; 95% CI, 0.41-0.68; p<0.00001, I(2) = 0%), as did disease free survival (DFS) (RR: 0.53; 95% CI, 0.43-0.66; p<0.00001, I(2)  = 0%). Exploratory subgroup analysis and sensitivity analysis revealed the similar results with original analysis. Conclusion ART therapy offers a safe and efficient alternative to SRT with longer 3-year and 5-year BFFS, better OS and DFS. Our recommendation is to suggest ART for patients with APFs and may reduce the need for SRT. Given the inherent limitations of the included studies, future well-designed RCTs are awaited to confirm and update this analysis.